Genetics of Greenbug Resistance in Synthetic Hexaploid Wheat Derived Germplasm - Crespo-Herrera, Leonardo; Singh, Ravi P.; Reynolds, Matthew; Huerta-Espino, Julio (Frontiers in Plant Science, 2019)
The greenbug, Schizaphis graminum Rondani, significantly reduces wheat, Triticum aestivum L., grain yields if not controlled. Host plant resistance can protect yield, is environmentally friendly and easy to use. Our objectives were to: 1) identify genomic regions associated with S. graminum resistance in a recombinant inbred lines population derived from the a cross of ‘Sokoll’ (resistant) and ‘Weebill1’ (moderately susceptible), 2) evaluate Sokoll derived breeding germplasm for resistance, and 3) conduct allelism tests between Sokoll and sources carrying resistance genes Gba, Gbb and Gbd. Resistance was measured qualitatively and quantitatively using a SPAD meter and visual assessments. We identified a large effect resistance gene on chromosome arm 7DL of Sokoll, herein referred as GbSkl, which contributed up to 24% of the phenotypic variation. Other minor QTL on chromosomes 2B, 3A and 7B were also identified. The QTL on 2B and 3A originated from Weebil1. Of the Sokoll derived germplasm, 13% displayed resistance. Allelism tests indicated that GbSkl could be allelic or tightly linked to the temporarily designated genes Gba, Gbb and Gbd. Utility of SPAD to determine quantitative variation in resistance phenotyping is demonstrated and breeding efforts are underway to transfer the resistance from Sokoll to new CIMMYT elite germplasm. This work was supported by the Bill & Melinda Gates Foundation, Grant Number OPPGD1389